Legal protection of the special rights of working women- a comparative study - Hadi Najim, lecturer Dr. Shamil (The college of law and political science journal, 2023)
The interest in regulating the rules of regulating women's work has increased as a result of the increased involvement of women in the labor market alongside men. And if the principle of contractual freedom requires the equality of women with men in work without discrimination, because each of them is called a worker in accordance with the text of Article (1/VI) of the Labor Law, which stipulates that the worker considers every person, male or female, who performs work for a wage. However, since the nature of women is different from that of men, and there are some jobs that do not conform to the nature of the working woman, the legislator has surrounded the work of women with some guarantees aimed at protecting women as they perform a double function.